A poesia de Helena Kolody: religiosidade em confluências da arte - Zanini, Ana Maria (2011)
The present study is dedicated to Helena Kolody s work. During her lifetime she was a substantiated poet and has been considered the most important female voice in the poetry from Paraná, she produced a remarkable poetry and she was the precursor of determined forms in the Brazilian literary history. The religiosity as the central axis pervades Kolody s work to meet significant and deep relations toward the theme of love. In a last moment, by approaching the intrinsic relation between the poetry and the image, a parallel is traced between Helena s and the painter and poet Marc Chagall s work. The work outlines the particular way used by Helena Kolody to lead to a view of transcendence from an impossible love.